Pelaksanaan Evaluasi Zona Integritas Menuju WBK dan WBBM Oleh Inspektorat Daerah Kota Malang (RechtJiva, 2025)
In writing this thesis, the author discussed the implementation of the evaluation and supervision of Integrity Zone development in Malang City. This topic was chosen due to the declining number of Regional Government Organizations (OPDs) in Malang City achieving the Corruption-Free Areas and Clean and Serving Bureaucracy Areas in Government Institutions predicates between 2022 and 2024. The writing of this paper uses a sociological juridical method. The author analyzes the legal material that gets by going directly to the location for collecting data and interviewing with the parties that related. The author analyzes it using descriptive analysis techniques by collecting the results of interviews and drawing conclusions. Based on the research results, using the previously mentioned research questions and methods, the author obtained answers to the problems regarding the implementation of the Integrity Zone evaluation and supervision by the Malang City Regional Inspectorate. Firstly, there is a lack of commitment from the work units involved in the ZI development. Secondly, the heavy workload of the work units prevents them from optimally fulfilling the ZI requirements. These problems resulted in work units failing to achieve the WBK and WBBM predicates, leading to a decrease in their number between 2022 and 2024.